2010
DOI: 10.1111/j.1743-7563.2010.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of daily filgrastim and pegfilgrastim to prevent febrile neutropenia in Asian lymphoma patients

Abstract: In Asian patients, pegfilgrastim prophylaxis did not show a therapeutic advantage for preventing neutropenic outcomes compared with filgrastim prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This study demonstrated that the incidences of breakthrough FN are relatively similar with the two agents (pegfilgrastim: 16.3% vs filgrastim: 13.6%, p ¼ 0.69) ( Table 1), and concluded that either G-CSF can be administered to NHL patients, with usage being largely guided by patient preference. 4 Although the study results have shown that filgrastim and pegfilgrastim have similar efficacies for the prevention of FN in NHL patients, approximately 15% may still experience breakthrough FN. Hence, another epidemiological study was performed to evaluate the risk factors associated with breakthrough FN among patients who received pegfilgrastim prophylaxis for CHOP-based chemotherapy.…”
Section: Specific Areas Of Workmentioning
confidence: 95%
See 1 more Smart Citation
“…This study demonstrated that the incidences of breakthrough FN are relatively similar with the two agents (pegfilgrastim: 16.3% vs filgrastim: 13.6%, p ¼ 0.69) ( Table 1), and concluded that either G-CSF can be administered to NHL patients, with usage being largely guided by patient preference. 4 Although the study results have shown that filgrastim and pegfilgrastim have similar efficacies for the prevention of FN in NHL patients, approximately 15% may still experience breakthrough FN. Hence, another epidemiological study was performed to evaluate the risk factors associated with breakthrough FN among patients who received pegfilgrastim prophylaxis for CHOP-based chemotherapy.…”
Section: Specific Areas Of Workmentioning
confidence: 95%
“…Comparison of efficacy between filgrastim and pegfilgrastim prophylaxis (adapted from Chan et al4 ).…”
mentioning
confidence: 99%
“…Patient data from four different studies (including patients with breast cancer and lymphoma receiving chemotherapy) were pooled in this analysis. [3][4][5][6] The data included demographics, disease-related and chemotherapy-related parameters, medical histories of other co-morbid diseases, as well as laboratory information reflective of hepatic, renal and hematological functions. Patients were treated with a variety of taxane-based, anthracycline-based and etoposidebased chemotherapy regimens.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…2 In Singapore, the incidence of FN among breast and lymphoma patients receiving myelosuppressive chemotherapies ranges from 6.3 to 25.0%. [3][4][5][6] Events resulting from FN may also be associated with an increased financial burden and risk of mortality. 7 The prophylactic use of granulocyte colony-stimulating factors (G-CSFs) can lead to a significant reduction of the incidence, duration and severity of chemotherapy-induced neutropenia and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Two pharmacoepidemiology studies that were conducted within Asian lymphoma patients demonstrated that, the incidence of breakthrough FN in lymphoma patients remained high even after receiving prophylactic pegfilgrastim, ranging from 13-16% [4,5]. It is unknown why lymphoma patients manifested breakthrough FN -whether it is due to the lack of adequate pegfilgrastim exposure or the lack of antimicrobial prophylaxis.…”
Section: Breakthrough Neutropenic Fever In Cancer Patientsmentioning
confidence: 99%